Debates in the Digital Humanities 2019 - Gold, Matthew K.; Klein, Lauren F. (Debates in the Digital Humanities, 2019)
The latest installment of a digital humanities bellwether Contending with recent developments like the shocking 2016 U.S. Presidential election, the radical transformation of the social web, and passionate debates about the future of data in higher education, Debates in the Digital Humanities 2019 brings together a broad array of important, thought-provoking perspectives on the field's many sides. With a wide range of subjects including gender-based assumptions made by algorithms, the place of the digital humanities within art history, data-based methods for exhuming forgotten histories, video games, three-dimensional printing, and decolonial work, this book assembles a who's who of the field in more than thirty impactful essays. Contributors: Rafael Alvarado, U of Virginia; Taylor Arnold, U of Richmond; James Baker, U of Sussex; Kathi Inman Berens, Portland State U; David M. Berry, U of Sussex; Claire Bishop, The Graduate Center, CUNY; James Coltrain, U of Nebraska-Lincoln; Crunk Feminist Collective; Johanna Drucker, U of California-Los Angeles; Jennifer Edmond, Trinity College; Marta Effinger-Crichlow, New York City College of Technology-CUNY; M. Beatrice Fazi, U of Sussex; Kevin L. Ferguson, Queens College-CUNY; Curtis Fletcher, U of Southern California; Neil Fraistat, U of Maryland; Radhika Gajjala, Bowling Green State U; Michael Gavin, U of South Carolina; Andrew Goldstone, Rutgers U; Andrew Gomez, U of Puget Sound; Elyse Graham, Stony Brook U; Brian Greenspan, Carleton U; John Hunter, Bucknell U; Steven J. Jackson, Cornell U; Collin Jennings, Miami U; Lauren Kersey, Saint Louis U; Kari Kraus, U of Maryland; Seth Long, U of Nebraska, Kearney; Laura Mandell, Texas A&M U; Rachel Mann, U of South Carolina; Jason Mittell, Middlebury College; Lincoln A. Mullen, George Mason U; Trevor Muñoz, U of Maryland; Safiya Umoja Noble, U of Southern California; Jack Norton, Normandale Community College; Bethany Nowviskie, U of Virginia; Élika Ortega, Northeastern U; Marisa Parham, Amherst College; Jussi Parikka, U of Southampton; Kyle Parry, U of California, Santa Cruz; Brad Pasanek, U of Virginia; Stephen Ramsay, U of Nebraska-Lincoln; Matt Ratto, U of Toronto; Katie Rawson, U of Pennsylvania; Ben Roberts, U of Sussex; David S. Roh, U of Utah; Mark Sample, Davidson College; Moacir P. de Sá Pereira, New York U; Tim Sherratt, U of Canberra; Bobby L. Smiley, Vanderbilt U; Lauren Tilton, U of Richmond; Ted Underwood, U of Illinois, Urbana-Champaign; Megan Ward, Oregon State U; Claire Warwick, Durham U; Alban Webb, U of Sussex; Adrian S. Wisnicki, U of Nebraska-Lincoln.